Tick Infection of Caiman crocodilus fuscus at the Hidroprado Hydroelectric Dam in Colombia: New Records, Parasite Prevalence, and Blood Loss Rate - Mora Rivera, Nohora Cristina (2020)
The main goal of this research was to identify the hard ticks (Acari: Ixodidae) found in 10 individuals of spectacled caiman (Caiman crocodilus fuscus) from 349 individuals captured at the Hidroprado hydroelectric dam in the Department of Tolima, Colombia. Parasite prevalence was 2.9%. A total of 40 ticks were collected and two species identified: Amblyomma dissimile (n = 39) and Rhipicephalus sanguineus (n = 1). This is the second record of A. dissimile in C. crocodilus in Colombia and the first record of R. sanguineus in crocodilians. The natural infection of C. c. fuscus by A. dissimile establishes this species as a host in the life cycle of this tick. Similarly, parasitism by R. sanguineus indicates C. c. fuscus as a potential host for this tick, which is important since it is associated with domestic animals and has a high potential for transmission of zoonotic diseases. Our results highlight the parasitic relationship between ticks and one of the most resistant wild vertebrates: caimans. The prevalence, although not high, establishes the potential of ticks to parasitize different species and to be a vector of diseases for new groups of hosts.